1988
DOI: 10.1063/1.1139702
|View full text |Cite
|
Sign up to set email alerts
|

Programmable instrumentation for high repetition rate experiments providing control in real time and acquisition of a train of pulses

Abstract: An automated, low-cost programmable instrumentation system which solves many of the problems associated with the data acquisition and control of high repetition rate experiments is described. The system can monitor and control experiments on a pulse-by-pulse basis while digitally storing consecutive pulses which occur in the train. The system compares well with manual test equipment and commercial transient diagnostic systems which cannot provide the high-speed control and data acquisition available here. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…This time duration is referred to as the repetitive stressing time (RST). Generally, the number of applied pulses, with a microsecond or millisecond pulse width, can be counted using a digital counter or specially designed equipment with automated data acquisition and control functions [12,23]. In the experimental investigation, the number of applied pulses was calculated by measuring the time duration, t RST .…”
Section: Signal Measurementmentioning
confidence: 99%
“…This time duration is referred to as the repetitive stressing time (RST). Generally, the number of applied pulses, with a microsecond or millisecond pulse width, can be counted using a digital counter or specially designed equipment with automated data acquisition and control functions [12,23]. In the experimental investigation, the number of applied pulses was calculated by measuring the time duration, t RST .…”
Section: Signal Measurementmentioning
confidence: 99%
“…Generally, the pulse number can be counted by a counter connected with the trigger modulator. [6,14] In this case, the number of applied pulses can be calculated and it is about the product of TBD and PRF. For the case in Fig.…”
Section: Measurement Results and Discussionmentioning
confidence: 99%
“…For example, for a repetitive µs-pulse breakdown, a programmable instrumentation system was needed to solve the problem of data acquisition. [14] It was found that the system could miss some pulses at a repetition rate above 40 Hz and the maximum applicable pulse repetition frequency (PRF) was 20 kHz. [14] Moreover, the instrumentation system needs some specially designed circuits which cannot be used in the measurement of repetitive nanosecond-pulse breakdown experiments directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, this verification is performed without any dependence with the radar manufacturer. In short, for timing requirements, a global positioning system (GPS) disciplined oscillator (GPSDO) is used [13], and for sampling and storing the signal for proper automatic processing, a high-frequency sampling oscilloscope is used [14]. In addition, a computer is used to get the data from the oscilloscope for analysis and signal processing.…”
Section: Introductionmentioning
confidence: 99%